Giving purpose to life among alcohol addicts who lead sober life - Markevičius, Giedrius (Psichologija, 2001)
Though alcohol addicts have been studied through the 'purpose of life' test quite much, peculiarities and problematics of their purpose of life when leading sober life have been studied little.The main aim of this article is to compare peculiarities of purpose of life of those alcohol addicts who have just started leading sober life and those who have been leading sober life for extended periods. For this, the level of purpose of life of both groups and level of inner coherence and its correlation with factors of purpose of life retrieved by means of factor analysis were quantitatively assessed; cognitive, motivational and emotional components of giving purpose to life as well as main difficulties and peculiarities of their solution are provided.After assessing the results of the research, it can be argued that the level of purpose of life and the level of inner coherence of those alcohol addicts who have just started leading sober life and those who have been leading sober life for extended periods statistically does not differ significantly, but the surveyed of the two groups differ in peculiarities of components of their giving purpose to life as well as in aspects of difficulties experienced and their solutions.Because level of inner coherence of only first group is related to one of factors of purpose of life, we raised a new hypothesis that capabilities to solve difficulties for those alcohol addicts who have just started leading sober life is one of the main factors in giving purpose to life. But this is a task for future research
Keywords: alcohol addicts; purpose; sober life